2022
DOI: 10.1039/d2sc02198f
|View full text |Cite
|
Sign up to set email alerts
|

All-in-one disulfide bridging enables the generation of antibody conjugates with modular cargo loading

Abstract: Tetra-divinylpyrimidine (TetraDVP) linkers offer a method for the generation of antibody conjugates with modular cargo loading and excellent stability via all-in-one disulfide bridging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“… 27 Dannheim et al also recently reported a disulfide re-bridging based method enabling access to PARs of 1, 2, 3 or 4, by employing linkers that connect four copies of divinylpyrimidine re-bridging agents (TetraDVP linkers), but have 1, 2, 3 or 4 terminal alkynes, respectively. 28 Noteworthy in this case however is that the modulation of loading does not come from modification of the bridging agent itself, but from using different linkers connecting multiple bridging agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 Dannheim et al also recently reported a disulfide re-bridging based method enabling access to PARs of 1, 2, 3 or 4, by employing linkers that connect four copies of divinylpyrimidine re-bridging agents (TetraDVP linkers), but have 1, 2, 3 or 4 terminal alkynes, respectively. 28 Noteworthy in this case however is that the modulation of loading does not come from modification of the bridging agent itself, but from using different linkers connecting multiple bridging agents.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Considering their pharmacokinetic and therapeutic inuence, broadening the scope of accessible DAR values for a payload/antibody couple is of great interest; (2) The homogenous DAR enabled by optimised antibody modications is typically limited to a single DAR. The few methods enabling a range of DARs all require incorporation of a different linker to access a different DAR, this constituting suboptimal modularity; 27,30,32 (3) To improve anti-tumour efficacy, overcome tumour resistance, or enable theranostic approaches, growing evidence indicates that combining different types of payloads on an ADC can have a positive effect. 33,34 However, apart from a few examples, methods reporting heterofunctionalisation of engineered, 31,[33][34][35] or native antibodies, [36][37][38] are limited; (4) Antibody fragments are underexploited for therapeutic purpose.…”
Section: Introductionmentioning
confidence: 99%
“…This technique of disulfide bridging can load one drug to each disulfide bond, generating ADCs with a controlled DAR of approximately 4 in IgG1s [26,27,28] . Developed disulfide bridging reagents include next generation maleimides (NGMs), [29,30,31] pyridazinediones (PDs), [32,33,34] bis‐sulfones, [35,36,37] divinylpyrimidines, [38,39] divinyltriazines, [39,40] arylenedipropiolonitriles, [41] dichlorotetrazines, [42] and others [43,44,45,46] …”
Section: Introductionmentioning
confidence: 99%
“…As an example, for complex diseases, ADCs with more than one cytotoxic payloads are highly sought after, to provide orthogonal modes of action [50] . New methods for dual‐modality bioconjugation broadly enable the incorporation of two different functionalities [51,52,53] and disulfide‐bridging dual‐conjugates have shown promising opportunities including the construction of bispecific conjugates, synthetic antibodies, and controlled‐loading antibody‐payload conjugates [54,55,56] . In this work, we aimed to explore a convenient trifunctional scaffold for DBM reagents, which would facilitate further research and applications of this reagent class.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Fab antibody fragments, which contain a single accessible interchain disulfide bond, have been very effectively targeted using such strategies for the construction of ADCs, imaging agents, bispecifics, and multifunctional conjugates. 3–6 A range of reagents have been developed to effect this bridging of disulfide bonds, 7 including next generation maleimides (NGMs), 8–10 pyridazinediones (PDs), 11,12 bis-sulfones, 3 divinylpyrimidines, 13,14 divinyltriazines, 15,16 arylenedipropiolonitriles, 17 dichlorotetrazines, 18 and others. 19–22 Whilst such reagents are valuable additions to the bioconjugation toolbox they often require multistep syntheses to access functionalised variants, and new strategies which expand the applications afforded by disulfide bridging and offer facile access to multifunctional conjugates, 23 are widely sought.…”
Section: Introductionmentioning
confidence: 99%